A Tri-Method Approach to a Review of Adventure Tourism Literature: Bibliometric Analysis, Content Analysis, and a Quantitative Systematic Literature Review. (August 2018) - Cheng, Mingming; Edwards, Deborah; Darcy, Simon; Redfern, Kylie
This article provides an objective, systematic, and integrated review of the Western academic literature on adventure tourism to discover the theoretical foundations and key themes underlying the field by combining three complementary approaches of bibliometric analysis, content analysis, and a quantitative systematic review. A total of 114 publications on adventure tourism were identified that revealed three broad areas of foci with adventure tourism research: (1) adventure tourism experience, (2) destination planning and development, and (3) adventure tourism operators. Adventure tourism has an intellectual tradition from multiple disciplines, such as the social psychology of sport and recreation. There is an underrepresentation of studies examining non-Western tourists in their own geographic contexts or non-Western tourists in Western geographic contexts. Our findings pave ways for developing a more robust framework and holistic understanding of the adventure tourism field.